TEACHER CHALLENGE: THE POSTMODER STUDENT - Alfaro Ramírez, Teresa (2011)
Societies progress: currently, a globalized and computer world, is a postmodern society. In it, the ways of transmitting and socializing culture have changed; new human beings have been developed postmodern individuals with very particular characteristics: they are our students. How to optimize the learning triad (student-teacher-knowledge)? It is not enough to know the contents and be a specialist in the field, it is essential to be aware of the current environment to analyze and understand the characteristics of our students, also called "sons of globalization" or "digital natives". Only then shall we know, also, our own reality as individuals and teachers. This paper seeks to analyze the characteristics of our students and reflect on our role as teachers in a complex and changing environment.